Perception of the Computer Engineering Students of Politeknik Negeri Samarinda on the Online Learning During Covid-19 Pandemic - Sektalonir Oscarini Wati Bhakti (Politeknik Negeri Samarinda, 2022)
ABSTRACTThe aim of the research is to find out the perception of the Computer Engineering Students of Politeknik Negeri Samarinda on the online learning during Corona Covid-19 pandemic. Purposive sampling technique was used in this research which the researchers only focused on the students who took English Subjects. The students were in the second and fourth semester who taking English for Computer Students in semester two and English Special Purposes in semester 2. The research data was the results of the filled questionnaire in the form of Google Form and spread online to their Line Group. Three main aspect of the questionnaire are learning and teaching aspect, the lecturers’ capability aspect, and facility and infrastructure aspect. In the first aspect, most of the students gave positive response to online learning can be easily accessed (83%). And for the second aspect, 71% oft the students gave positive response to the lectures are always with students during online learning. Meanwhile, for the facility and infrastructure aspect, 63% students said that they have adequate devices to do online learning but this is the opposite to the statement that the students have the internet connection in conducting online learning (57%)